Laminar composites - Staab, George H.; ScienceDirect eBooks (Kidlington, Oxford : Butterworth-Heinemann is an imprint of Elsevier, 2015)
"Laminar Composites presents the subject from a mechanics point of view. Topics are developed at a level suitable for upper-level undergraduate students and beginning graduate students."--Jacket.
Introduction to Composite Materials -- Historic and Introductory Comments -- Characteristics of a Composite Material -- Composite Materials Classifications -- Fundamental Composite Material Terminology -- Advantages Afforded by Composite Materials -- Selected Manufacturing Techniques for Composites -- A Review of Stress, Strain, and Material Behavior -- Strain--Displacement Relations -- Strain Transformations -- Stress and Stress Transformations -- Stress--Strain Relationships -- Monoclinic Materials -- Orthotropic Materials -- Transversely Isotropic Materials -- Isotropic Materials -- Summary of Material Responses -- Strain--Stress Relationships -- Thermal and Hygral Effects -- Complete Anisotropic Response -- Lamina Analysis -- Mechanical Response of Lamina -- Stiffness Matrix -- Transformation of Stresses -- Plane Stress Analysis -- Thermal and Hygral Behavior of Lamina -- Thermal Stress--Strain Relationships -- Hygral Effects -- Prediction of Lamina Properties (Micromechanics) -- Mechanical Properties of Lamina -- Physical Properties and Strength Estimates -- Mechanical Test Methods for Lamina -- Strain Gages Applied to Composites -- General Interpretation of Strain Gage Data -- Strain Gage Misalignment -- Strain Gage Reinforcing Effects -- Experimental Determination of Mechanical Properties -- Tensile Testing -- Compression Testing -- Shear Tests -- Flexure Tests -- Failure Strengths -- Physical Properties -- Density -- Fiber Volume Fraction -- Thermal Expansion and Moisture Swelling Coefficients.
Online resource; title from PDF title page (Ebsco, viewed Aug. 14, 2015).
Includes bibliographical references and index.
Elsevier
Keywords: Laminated materials; Composite materials; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; Composite materials; Laminated materials; Electronic books